As vivências de pessoas adultas com transtorno do espectro autista na relação com a escolaridade e concepções de mundo - Bittencourt, Ivanise Gomes de Souza (2018)
This study analyzed the experiences of adults with Autism Spectrum Disorder (ASD) in relation to their schooling and world conceptions, in order to highlight aspects that have potentiated and/or weakened their development and social participation. The historical-cultural approach of Vygotski constituted the theoretical contribution of this research, which used the life narrative and had as unit of analysis the experience. The study was conducted between 2016 and 2017 with 8 (eight) participants: 4 (four) individuals diagnosed with ASD, aged between 30 and 36 years, three males and one females who were enrolled in one CAPS in the municipality of Maceió-Alagoas, and their mothers between the ages of 53 and 68 years. The diagnosis of ASD of the participants was defined in varied phases, such as adolescence, youth and adulthood. The data were produced from narrative interviews, initially with the mothers and later with the participants with ASD. And, given the diversity of the communicative skills of people with ASD, the Alternative Communication System for Literacy of People with Autism (SCALA) was used, an assistive technology, from a supplementary form, from its Visual Narratives module. The participants with TEA produced their life histories from the following topics suggested to them: Who am I ?, My family, The school, CAPS, Autism, The future and, in some cases, The University / Faculty and Job. The data were organized in six (6) thematic units with discussion on: social reality in relation to late diagnosis of ASD, challenges for schooling, family as a reference in school trajectories, CAPS in the reception and meeting of the participants with the TEA, the challenges to social life and the absence of public policies that ensure them in adulthood with ASD and the experiences in the relationship in how they perceive themselves, autism and the future. It was verified that the experiences of the participants with ASD, in their family, school and social spaces, reflected in their schooling and world conceptions, with impacts on the development, constitution, social position and their appropriations and activities in the world. They experienced the weaknesses of unprepared professionals for the definition of early diagnosis of ASD and treatments, the school system to deal with them in their specificities and society in accepting them and include them in social life. However, the potential of family mobilization for school and social inclusion and the CAPS as a space of reception, socialization and overcoming exclusion, were the foundations of life. As the participants with ASD were part of the Social Development Situation (SSD) and their relations with the environment, the situations and events experienced influenced the psychological development and were guiding them in their positions and their personal characteristics.